Addiction : from biology to drug policy - Goldstein, Avram (Oxford ; New York : Oxford University Press, 2001)
1. Introduction. PART ONE: DRUGS AND THE BRAIN. 2. Neurotransmitters: The Brain's Own Drugs. 3. Receptors: Locks for the Addictive Keys. 4. Addictive Behavior. 5. Pain and Pleasure. 6. The Seesaw Brain: "Highs" and Adaptations. 7. Are Addicts Born or Made?. PART TWO: DRUGS AND THE ADDICTS. 8. Nicotine. 9. Alcohol and Related Drugs. 10. Heroin, Morphine, and Other Opiates. 11. Cocaine and Amphetamines. 12. Cannabis (Marijuana). 13. Caffeine. 14. Hallucinogens. PART THREE: DRUGS AND SOCIETY. 15. Prevention: Just Say No?. 16. Treatment Addiction, Preventing Relapse. 17. Three Lessons fr.
Drugs and the brain. Neurotransmitters : the brain's own drugs -- Receptors : locks for the addictive keys -- Addictive behavior -- Pain and pleasure -- The seesaw brain : "highs" and adaptations -- Are addicts born or made? The drugs and the addicts. Nicotine -- Alcohol and related drugs -- Heroin, morphine, and other opiates -- Cocaine and amphetamines -- Cannabis (Marijuana) -- Caffeine -- Hallucinogens. Drugs and society. Prevention : just say no? -- Treating addiction, preventing relapse -- Three lessons from the street -- Three lessons from abroad -- Prohibition vs. legalization : a false dichotomy -- New strategies for rational drug policy.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Drug addiction; Drug abuse -- Social aspects; Medical policy; Drug abuse; Substance-Related Disorders -- physiopathology; Brain -- drug effects; Health Policy; Illicit Drugs -- adverse effects; Substance-Related Disorders; Toxicomanie -- Aspect physiologique; Toxicomanie -- Aspect social; Toxicomanie; Politique sanitaire; drug abuse; drug addiction; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); MEDICAL -- Neurology; Medical policy; Drug abuse; Drug abuse -- Social aspects; Drug addiction; Soziologie; Drogenabhängigkeit; Physiologie; Drugsverslaving; Drugsbeleid